Seismic energy demands of steel special moment frames - Dogru, Selcuk; Akbaş, Bülent (Gazi Univ, Fac Engineering Architecture, 2020)
It is known that a structure is expected to behave nonlinearly when subject to strong ground motions. For evaluating the nonlinear seismic response of the structural system, one of the most reliable ways is to use energy based approach. Energy based design can be expressed as the balance of energy input and the energy dissipation capacity of the structure. Energy based studies have been usually done for single degree of freedom systems. Studies are needed for real structures in multi degree of freedom systems (MDOFs) in framework of the energy based design methodology. The aim of this paper is to determine seismic energy demands in steel special moment frames that have various height levels and span lengths for the evaluation of energy-based approach in the framework of performance-based design. Low, medium and high-rise steel special moment frames are examined using linear and nonlinear dynamic time history analyses. The results are evaluated to obtain inelastic hysteretic energy distribution and energy demand spectrum.It is shown that total input energy and total hysteretic energy is not a constant value and depends on the properties of the structure and ground motion properties.
Süneklik düzeyi yüksek moment aktaran çelik çerçevelerin sismik enerji istemleri
Keywords: Energy spectrum; energy based design; energy distribution; steel moment frames; earthquake resistant design